EFFECT OF PARENTS’ WORK ON STUDENTS’ LEARNING ACHIEVEMENT: (A Case Study at SDN Kedungpandan 2, Jabon Subdistrict, Sidoarjo Regency) - Nurul Rohmah; Devita Sulistiana; Ida Putriani (JOSAR (Journal of Students Academic Research), 2019)
This study aims to investigate the effect of parents’ work on students’ learning achievement at SDN Kedungpandan 2, Jabon subdistrict, Sidoarjo regency. This research was carried out in the odd semester of 2019-2020 academic year to students of grade I-VI consisting of 109 students. The sample used was a strata sample comprising of 86 students. The type of research used was quantitative research with descriptive approach. This research was a causal association ex post facto research. The data were collected through documents and interviews. Data analysis technique adopted t test. T test result was 5.28 with a significance level of 0.05, while the t table in this study was 2.643. Therefore, Ha was accepted and Ho was rejected. The result of this study indicates that there is an effect of parents’ work on students’ learning achievement at SDN Kedungpandan 2